2016
DOI: 10.3233/thc-161164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoking on spinal fusion after spondylodesis surgery: A comparative clinical study

Abstract: The results indicate that smoking adversely effects spinal fusion. Particularly re-operations caused by pseudarthrosis occur at a higher rate in smokers than in non-smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 20 publications
0
36
0
2
Order By: Relevance
“…In the present study, the perioperative complication rates were within the range reported for MIS in the literature and were lower than those reported for patients undergoing open posterior lumbar spinal fusion surgeries. Previous studies have demonstrated that complication rates of MIS did not differ between younger and elderly patients and that the surgical success of MIS in terms of functional outcome did not differ between smokers and non‐smokers. Avila et al .…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, the perioperative complication rates were within the range reported for MIS in the literature and were lower than those reported for patients undergoing open posterior lumbar spinal fusion surgeries. Previous studies have demonstrated that complication rates of MIS did not differ between younger and elderly patients and that the surgical success of MIS in terms of functional outcome did not differ between smokers and non‐smokers. Avila et al .…”
Section: Discussionmentioning
confidence: 95%
“…39 Hermann et al showed that fusion success in nonsmokers is greater than smokers and that reoperation rates caused by pseudarthrosis were greater in smokers. 44 The nonunion results in smokers are not necessarily uniform across all lumbar fusion studies. Bydon et al obtained results that were consistent with the above findings for pseudarthrosis after 2-level posterolateral fusions, but not necessarily on single-level PLF.…”
Section: Lumbar Fusion Outcomes In Smokersmentioning
confidence: 99%
“…Multiple studies have also shown a negative effect of smoking on the outcomes of lumbar surgery. [27][28][29][30] In the multivariate analysis, however, smoking did not show any statistical significance, which could be due to our small sample size. Sex, body mass index, and history of alcohol abuse were not predictors in our study.…”
Section: Discussionmentioning
confidence: 63%